The Grammatical Functions of Korean Sentences in Yun Dong Ju’s Poem Titled 길 (Gil/The Road) and its Indonesian Equivalent - Lia Amelia Nurkhazanah; Ypsi Soeria Soemantri; Wagiati Wagiati; Puspa Mirani Kadir (Makassar State University, 2022)
Abstract. The aim of this study is to compare the grammatical functions contained in Yun Dong Ju's poem entitled 길 (Gil/The Road) in the book Puisi untuk Rakyat Indonesia (Poetry for Indonesian People) translated by Chung Young Rim. The data were analyzed based on the syntactic structure in the source language, which is Korean, and its translation into the target language, which is Indonesian, to implement the study of syntactic theory and its application in the field of comparative literary translation. The method of this research was descriptive contrastive qualitative. Meanwhile, the data collection techniques were observing and taking notes. First of all, the researchers explained the grammatical functions contained in the poem both in Korean and Indonesian, and then compared the syntactic function data. The results of the study on Yun Dong Ju’s poem entitled (Gil/ The Road) that focused on the comparison between the grammatical functions in the source language and those in the target language showed that there are 4 times occurrence of the addition of subjects and 1 time occurrence of the addition of adjunct in the target language; 5 changes in grammatical functions, 4 deletions of grammatical functions in the target language, and 2 diction differences in grammatical functions. Furthermore, there are 2 data that show no changes in in its grammatical functions. The changes in the syntactic structure found in Yun Dong Ju’s poem entitled길 (Gil/The Road) occurred to avoid ambiguity in conveying meaning since in Indonesian, clear subjects and adjuncts are needed. Therefore, the translation system tends to be broader than the source language.Keywords: Syntax, Grammatical Functions, Poem, Korean, Indonesian